If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 96 + x = 40x Solving 96 + x = 40x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-40x' to each side of the equation. 96 + x + -40x = 40x + -40x Combine like terms: x + -40x = -39x 96 + -39x = 40x + -40x Combine like terms: 40x + -40x = 0 96 + -39x = 0 Add '-96' to each side of the equation. 96 + -96 + -39x = 0 + -96 Combine like terms: 96 + -96 = 0 0 + -39x = 0 + -96 -39x = 0 + -96 Combine like terms: 0 + -96 = -96 -39x = -96 Divide each side by '-39'. x = 2.461538462 Simplifying x = 2.461538462
| 5x+100=-235 | | -6s=36 | | y=(1-x)/1.2 | | (x+7)(x-2)=(x+1)(x+1) | | 1.4(x+1.2)=7.8 | | -24/5=31/2h | | (x+7)(x+2)=(x+1)(x+1) | | m=z+bx | | 12x+8y+7x=z | | 2(3x-4)+6(x-5)=-3(4-5x)+5x-16 | | 4y-1x+2y=z | | [8+(-4)]-5= | | -8/12-21/12 | | 12+[-5+(-4)]= | | (7/x)-(1/7)=(2/x) | | 3(3x-2)=15 | | 2(3x-5)+6(x-3)=-3(3-5x)+5x-1 | | 2-4(x+3)=4-2(3x+5) | | 2.5=2/s | | -2(-3)-5y=4 | | -2y-42=3(y+1) | | -2/3(6*3-45)-2(3) | | 9x+2x=0x | | 21-u=17 | | 3x^2-4y=7 | | 2/5*15-1=5 | | (6a+1)(5a+2)= | | 5x-(4x+5)=3x-33 | | 441800*8*5/12 | | 992400*8*5/12 | | -16/n=32 | | 7X-3=4+6X |